ANALISIS PERUBAHAN KEBIJAKAN LUAR NEGERI TIONGKOK DALAM MERESPONS KEBERADAAN THAAD DI KOREA SELATAN - Antania, Teresa; Fasisaka, Idin; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 2 (2019), 2019)
ABSTRACT This research aims to explain the change in China’s response regarding the deployment of THAAD in South Korea. THAAD is one of United States – South Korea cooperation in order to deter North Korea, but China also views the THAAD as a threat to its national security. China retaliated with a boycott towards South Korea in 2016, but then decided to normalize its relations with South Korea at the end of 2017 even though THAAD is still deployed in South Korea. The theoretical framework in this research used liberalism’s economic interdependence theory to analyze this case, with further explanation using trade-peace model. This research found that the reason behind China’s change of response regarding THAAD was based on a tendency to maintain its economic relations with South Korea.   Keywords: China-South Korea relations, THAAD boycott, economic interdependence, trade-peace model